Catalytic Activity of Anisotropic Gold Nanoplates towards Oxygen Reduction. Issue 10 (13th August 2019) - Opuchlik, Lidia Jagoda; Kizling, Michal; Bacal, Pawel; Bilewicz, Renata
Abstract: Glassy carbon electrode (GCE) coated with anisotropic gold nanoplates (aAuNPs) was used for the study of oxygen reduction reaction (ORR) in 0.5 M sulfuric acid instead of bulk gold electrodes. The electrode cleaning/activation procedure lead to the removal of any charged and uncharged residues on the gold nanoplates, leaving the nanostructured surface highly active towards oxygen reduction. The advantages: much lower overpotential and larger current densities of oxygen reduction are ascribed to the unique nanostructures present on the carbon electrode surface‐the gold nanoplates. They are rich in edges providing a large population of Au (100) sites with unsaturated coordination exposed to the solution, and catalytically active. Measurements performed using a rotating disc electrode, modified with the gold nanoplates, confirmed that ORR proceeds via two separate steps: oxygen is reduced to hydrogen peroxide, and the peroxide is further reduced in a two‐electron reduction to water. Abstract :